Membangun Kompetensi Petani Padi melalui Pelatihan Partisipatif dalam Produksi Pupuk Organik - Zulkifli, Lutfi; Setyaningrum, Agustinah; Budiyoko, Budiyoko; Rachmah, Malinda Aptika (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
The Gatos Farmers’ Group, as a pioneer of organic rice cultivation in Sumpiuh, has faced challenges due to the limited availability of high-quality and affordable organic fertilizers. At the same time, goat manure generated from local livestock farming has not yet been optimally utilized. This community service activity was designed to enhance farmers’ capacity in processing goat manure into organic fertilizer through participatory training. A total of 25 organic rice farmers, all members of the Gatos Farmers’ Group, took part in this program. The method consisted of three stages: preparation (observation and focused group discussions), implementation (technical training and hands-on practice), and post-training assistance. Evaluation results indicated a 41% increase in participants’ understanding, as reflected in the comparison of pre-test and post-test scores. The participatory training approach not only improved the knowledge and technical skills of organic rice farmers in producing their own organic fertilizer but also fostered the integration of crop–livestock farming systems that support the application of a circular economy at the local level.ABSTRACTKelompok Tani Gatos sebagai pionir budidaya padi organik di Kelurahan Sumpiuh, Kabupaten Banyumas, menghadapi kendala keterbatasan pupuk organik berkualitas dengan biaya terjangkau. Di sisi lain, limbah kotoran kambing dari peternakan masyarakat belum dimanfaatkan secara optimal. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan kapasitas petani dalam mengolah kotoran kambing menjadi pupuk organik melalui pelatihan partisipatif. Kegiatan pengabdian kepada masyarakat ini melibatkan 25 orang petani padi organik yang merupakan anggota Kelompok Tani Gatos. Metode yang digunakan meliputi tiga tahap, yaitu persiapan (observasi dan diskusi terarah), pelaksanaan (pelatihan teknis dan praktik langsung), serta pendampingan pasca-pelatihan. Hasil evaluasi menunjukkan peningkatan pemahaman peserta sebesar 41% berdasarkan perbandingan nilai pre-test dan post-test. Kegiatan pelatihan dengan pendekatan partisipatif ini berhasil pengetahuan dan keterampilan petani padi organik dalam memproduksi pupuk organik mandiri, sekaligus menciptakan integrasi pertanian-terpadu yang mendukung ekonomi sirkular di tingkat lokal.